Nilai-Nilai Kearifan Lokal Kesenian Beluk di Kampung Adat Kuta Kecamatan Tambaksari Kabupaten Ciamis - Apriani, Nita Dewi Putri; Sondarika, Wulan; Sudarto, Sudarto (Jurnal Artefak, 2025)
Beluk art is closely related to wawacan literature which is still preserved by the Kuta village community. This art is estimated to have existed when Nyi Dewi Sri or Nyi Pohaci told how to farm, because rice is a source of human life. However, lately, beluk art has been rarely played by the younger generation, they generally do not know this traditional music. This study aims to describe the values of local wisdom of Beluk art in the Kuta - Ciamis Traditional Village. The method used is a qualitative ethnographic method through the steps of observation, interviews and documentation. The results of the study indicate that Beluk art has a value that is deeply rooted in the traditions of the Kuta Village community, this is because the area is an area that is backed by an agricultural community. This art has existed since long ago which is used as a performance when cutting rice. In the 2000s, this art was rarely performed because there was no young generation who wanted to continue it. So the development of this art began to fade. In the past, this art only focused on cutting rice which was always carried out during the harvest season, but now this art is performed during certain events. The values contained in it include religious values, socio-cultural, historical, aesthetic, creative, national spirit, love of the homeland, togetherness, environmental preservation, education, cultural identity, and the value of simplicity.